A Study of Mathematical Creative Thinking Ability of Senior High School Students Through Alberta Inquiry Learning Model at Siak Watershed Area, Riau Province - Kartini, Kartini; Yuanita, Putri; Siregar, Syarifah Nur (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The research is aimed at examining mathematical creative thinking ability of senior high school students using Alberta inquiry learning model and conventional learning method in Siak watershed, and disseminating Alberta inquiry learning model. This quasi-experimental research used nonequivalent control group design. The research population was senior high school students in Siak watershed, Riau Province. Forty-six students of grade X were chosen as the samples. The data were analyzed using t-test. The research results showed that studentsâ mathematical creative thinking ability was better increased through the use of Alberta inquiry learning model compared to conventional learning methods.